A Critical Review of Factors Affecting Manpower and Equipment Productivity in Tall Building Construction Projects - Parthasarathy, Mudumbai Krishnaswamy; Murugasan, Rajiah; Murugesan, Kavitha (Penerbit Universiti Sains Malaysia, 2017)
Developing countries have seen an increase in construction of tall buildings in metropolitan cities due to space constraint. The construction of tall buildings in developing countries is undertaken as a combination of manpower and equipment to economize costs. This combination or interface of manpower and equipment, particularly in the basic activities such as concreting, reinforcement, formwork, blockwork, and plastering affects productivity of both the resources. This research aims at studying the factors affecting productivity of manpower and equipment at the micro level for the basic activities of construction for tall building projects. The factors have been further grouped and combined as sections. Responses collected through questionnaire survey from 109 personnel associated with the construction of 72 tall buildings in different geographies of India have been analysed using theoretical tools like frequency index, Spearman's rank correlation coeffcient, and factor analysis. The factors have been prioritized in descending order of frequency indices. Based on analysis, it is found that factors in human and planning groups are more inﬂuential and affect manpower and equipment productivity signifcantly. Contract managers and cost engineers can use this study to make allowance while analysing productivity and estimating costs for tall buildings having combined usage of manpower and equipment.